2018
DOI: 10.1186/s13287-018-0799-z
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activation of TAZ enhances osteogenic differentiation and bone formation of adipose-derived stem cells

Abstract: BackgroundAdipose-derived stem cells (ADSCs) are an attractive cell source for bone tissue engineering and have great potential for bone regeneration and defect repair. The transcriptional coactivator with PDZ-binding motif (TAZ) has been demonstrated to modulate osteogenic and adipogenic differentiation of mesenchymal stem cells. However, its roles during ADSC differentiation and therapeutic potentials for bone regeneration have as yet not been well established.MethodsTAZ expression was measured during osteog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 45 publications
3
30
0
Order By: Relevance
“…As a transcriptional coactivator in the Hippo signaling pathway, transcriptional coactivator with Tafazzin (TAZ) plays a regulatory role in the Wnt signaling pathway [20]. A previous study confirmed the functions of TAZ, such as its mediation of the osteogenic differentiation of adipose-derived stem cells [21]; remarkably, TAZ obviously accelerated the osteogenesis of BMSCs through increasing the expression of RUNX2, a key transcription factor in the BMP and Wnt/β-catenin pathways [22,23]. All these findings indicate that TAZ serves as a vital osteogenesis mediator in BMSCs.…”
Section: Introductionmentioning
confidence: 94%
“…As a transcriptional coactivator in the Hippo signaling pathway, transcriptional coactivator with Tafazzin (TAZ) plays a regulatory role in the Wnt signaling pathway [20]. A previous study confirmed the functions of TAZ, such as its mediation of the osteogenic differentiation of adipose-derived stem cells [21]; remarkably, TAZ obviously accelerated the osteogenesis of BMSCs through increasing the expression of RUNX2, a key transcription factor in the BMP and Wnt/β-catenin pathways [22,23]. All these findings indicate that TAZ serves as a vital osteogenesis mediator in BMSCs.…”
Section: Introductionmentioning
confidence: 94%
“…TAZ, a transcriptional co‐activator regulated by interactions with 14‐3‐3 and PDZ domain proteins, has been shown to promote osteogenic differentiation of MSCs . Stimuli that promote bone formation transcriptionally up‐regulate TAZ, including LPS used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…SH3BP2 is important for the activation of the tyrosine kinase ABL, essential for osteoblast differentiation together with the transcriptional coactivator TAZ 4 . Tankyrase inhibitors were found to increase SH3BP2 and the nuclear expression of ABL, TAZ, and RUNX2 in murine primary calvaria cells, which consequently activated the ABL-TAZ complex, and therefore enhanced the osteoblast differentiation and maturation evidenced by the significant increase in the expression of osteoblast differentiation genes and mineral deposition 4,[20][21][22] . However, the mechanism of Tankyrase signaling in bone metabolism remains to be elucidated.…”
mentioning
confidence: 98%